2019
DOI: 10.32479/ijeep.8282
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Environmental Uncertainty, Ais Efficiency and Energy Efficiency With Environmental and Operational Performance in Indonesia

Abstract: Focusing on the current environmental era, the present study aims to evaluate the role of accounting and environment in driving the firm's performance. Therefore, the study is motivated to evaluate the specific relationship of energy efficiency, accounting information system efficiency and environmental uncertainty with business performance. The current study measures the empirical impact of the performance drivers on two vital domains of a firm's performance. The results of partial least square structural equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…According to the findings of the first hypothesis test, performance (KN) is negatively impacted by environmental uncertainty (KL). These findings are consistent with those of Aprisma and Sudaryati (2020), Sajilan et al (2019), andSingh (2019). This indicates that the high level of environmental uncertainty (KL) that occurred during the COVID-19 pandemic has triggered a decline in performance (KN).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…According to the findings of the first hypothesis test, performance (KN) is negatively impacted by environmental uncertainty (KL). These findings are consistent with those of Aprisma and Sudaryati (2020), Sajilan et al (2019), andSingh (2019). This indicates that the high level of environmental uncertainty (KL) that occurred during the COVID-19 pandemic has triggered a decline in performance (KN).…”
Section: Discussionsupporting
confidence: 87%
“…Uncertainty in the environment is the absence of knowledge about environmental factors that have an impact on a company's performance (Chen, 2013). Empirical findings showed that environmental uncertainty affects firm performance (Aprisma & Sudaryati, 2020;Sajilan et al, 2019;Singh, 2019;Mukherji & Mukherji, 2017;Abdallah & Persson, 2014;Bastian & Muchlish, 2012;Sung et al, 2010). According to Mukherji and Mukherji (2017), Abdallah and Persson (2014), Bastian and Muchlish (2012), and Sung et al (2010), high levels of environmental uncertainty have a positive effect on company performance.…”
Section: Environmental Uncertainty and Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In the era of firms in the direction of a green firm, accountants have an important factor in changing the views of the firm because accountants have to present information on the firm's operations in the form of financial statements, including if there are environmental activities carried out by the firm. So from that reporting carried out must be based on environmental accounting (Meiryani et al, 2018;Sajilan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%